805 Musculoskeletal complaints among office workers: complementary role of physical, psychosocial and environmental job demands and resources. (24th April 2018) - Daenen, Liesbeth; Elst, Tinne Vander; Hermans, Veerle; Verbeek, Chris; Verwimp, David; Godderis, Lode
Abstract : Introduction: Work-related musculoskeletal disorders (WMRDs) are the most important causes of work disability and long-term absenteeism among office workers. A wide range of risk factors of physical, psychosocial and environmental nature has been identified, but the question remains as to which degree these factors contribute to WMRDs and which explanatory mechanism underlies this relationship. Therefore, an integrated model corresponding to the scientific literature and the Job Demands-Resources model was used to examine (1) the effects of both job demands (e.g. workload, prolonged sitting, glare/reflection) and job resources (e.g. social support, accurate workplace settings) on WMRDs and (2) the mediating role of emotional exhaustion and cognitive stress complaints in the relationship between these job demands/resources and WMRDs in office workers. Methods: Thousand office workers from several Belgian companies participated in the study. They were asked to fill out a structured online questionnaire including socio-demographic characteristics, work-specific factors and job demands/resources covering four work-related domains (i.e. work experience, workstation, work environment and movement). Path analysis by means of Mplus 7.4 was conducted to test the hypotheses. Results: Most commonly reported complaints were located in the back (48%) and neck (34%). Multiple direct effects were found between measured job demands/resources and WMRDs, but only lower levels of social support predicted self-reported pain at all body regions (p<0.05). Regarding the indirect effects, emotional exhaustion was the most important mediator as it mediated the relationships between workload, noise, social support, autonomy, and WMRDs (k 2 values from 0.02 to 0.07). Discussion: The results indicate that (1) physical, environmental as well as psychosocial job demands/resources are related to WRMDs and (2) emotional exhaustion is an important explanation. These association and mediation patterns suggest opportunities for intervention strategies in order to stimulate accurate workplace settings, improve work experience (with special attention to social support) and prevent emotional exhaustion.